Market surveys in Mataram, Lombok, illustrate the expanse of legal and illegal Indonesian bird trade networks - Boyd T. C. Leupen; Loretta Shepherd; Chris R Shepherd; Evros Damianou; Vincent Nijman (Universitas Pakuan, 2022)
Bird keeping is deeply rooted in Indonesian culture and markets selling large numbers of birds are found across the country. We examined bird markets in Mataram on the island of Lombok. Across five market visits, 10,326 birds of 108 species were observed, with 18 of these species being nationally protected and 10 having been assessed as globally threatened by the IUCN Red List of Threatened Species. Observed protected species, as well as non-protected species with no or exceeded harvest quotas accounted for a total of 8,586 (83.1%) illegally traded birds. In terms of trade volume, 80.8% (n=8,347) of the recorded Indonesian birds were native to Lombok, suggesting that many of the birds for sale were sourced locally. However, 63% (n=65) of the encountered Indonesian species were not native to Lombok, confirming previously described intra-national bird trade flows between the Indonesian islands. We found a strong positive relation between a species’ body size and its asking price. Current legislation in Indonesia is sufficient to eradicate the open trade in illegally sourced and/or protected species. Improved enforcement of these laws, in combination with strategic demand reduction efforts, is needed to curb illegal and unsustainable bird trade in the country.